Jati Inequality in Rural Bihar - Joshi, Shareen; Kochhar, Nishtha; Rao, Vijayendra (World Bank, Washington, DC, 2018)
Caste is a persistent driver of inequality in India, and it is generally analyzed with government-defined broad categories, such as Scheduled Caste and Scheduled Tribe. In everyday life, however, caste is lived and experienced as jati, which is a local system of stratification. Little is known about economic inequality at the jati level. This paper uses data from poor rural districts in Bihar to explore expenditure inequality at the jati level. Inequality decompositions show much more variation between jatis than between broad caste categories. The analysis finds that even within generally disadvantaged Scheduled Castes and Scheduled Tribes, some jatis are significantly worse off than others. Consistent with previous work, the paper also finds that inequality is largely driven by inequality within jatis. This finding has implications for the implementation of large-scale poverty alleviation programs: the benefits of programs intended for disadvantaged castes are concentrated among specific jatis.